Probabilistic Composition of Preferences, Theory and Applications - Parracho Sant'Anna, Annibal (Springer, 2015)
Putting forward a unified presentation of the features and possible applications of probabilistic preferences composition, and serving as a methodology for decisions employing multiple criteria, this book maximizes reader insights into the evaluation in probabilistic terms and the development of composition approaches that do not depend on assigning weights to the criteria.